2019
DOI: 10.1002/biof.1542
|View full text |Cite
|
Sign up to set email alerts
|

The role of epigenetic changes in preeclampsia

Abstract: Preeclampsia (PE) is a disorder affecting 2–10% of pregnancies and has a major role for perinatal and maternal mortality and morbidity. PE can be occurred by initiation of new hypertension combined with proteinuria after 20 weeks gestation, as well as various reasons such as inflammatory cytokines, poor trophoblast invasion can be related with PE disease. Environmental factors can cause epigenetic changes including DNA methylation, microRNAs (miRNAs), and histone modification that may be related to different d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 133 publications
3
46
0
Order By: Relevance
“…Posttranslational modification of histones involves covalent modification of specific sites and residues that form specific three-dimensional arrangements of nucleosomes that control the accessibility to transcriptional factors to genes to induce gene expression. Histones are primarily modified at basic lysine and arginine residues, thereby marking active and inactive chromatin states [8]. Important histone modifications include acetylation, methylation, phosphorylation, and ubiquitination.…”
Section: Introductionmentioning
confidence: 99%
“…Posttranslational modification of histones involves covalent modification of specific sites and residues that form specific three-dimensional arrangements of nucleosomes that control the accessibility to transcriptional factors to genes to induce gene expression. Histones are primarily modified at basic lysine and arginine residues, thereby marking active and inactive chromatin states [8]. Important histone modifications include acetylation, methylation, phosphorylation, and ubiquitination.…”
Section: Introductionmentioning
confidence: 99%
“…The placenta is the most hypomethylated DNA in human tissue, and DNA methylation increases specifically with gestational age [38], coupled to a high demand for methionine in the third trimester of pregnancy [39]. A striking observation confirms the link between elevated circulating homocysteine, oxidative stress, and methylation [40][41][42]. Homocysteine is both a cause and a consequence of oxidative stress, which can lead to pre-eclampsia [43] A further observation has shown that the oxygen load delivered during parturition in order to stabilize preterm babies affects their methylome.…”
Section: Blastocyst Formation Implantation and Placental Developmentmentioning
confidence: 55%
“…It is not known whether the process is reversible, and the authors [44] suggest that this could affect the response to oxidative stress, DNA repair, and cell progression. Ultimately, placental growth is intricately linked to DNA methylation [40], and correct homeostasis to allow effective methylation avoids adverse pregnancy outcomes such as pre-eclampsia [41][42][43][44][45][46].…”
Section: Blastocyst Formation Implantation and Placental Developmentmentioning
confidence: 99%
“…9 miRNAs can regulate cell physiological processes, inhibit trophoblast apoptosis, and regulate transcription, translation and signal transduction of placenta-related genes. 10,11 The abnormal expression of miRNAs is closely related to the abnormal placental formation, which greatly increases the risk of the development of PE. 12 It was found that the expression of miR-20a was up-regulated in placenta of PE patients.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of small non‐coding RNAs that regulate cell proliferation, differentiation and apoptosis by binding to the 3'‐untranslated region (UTR) of target mRNAs 9 . miRNAs can regulate cell physiological processes, inhibit trophoblast apoptosis, and regulate transcription, translation and signal transduction of placenta‐related genes 10,11 . The abnormal expression of miRNAs is closely related to the abnormal placental formation, which greatly increases the risk of the development of PE 12 .…”
Section: Introductionmentioning
confidence: 99%